Comparison of the New Viscoelastic Coagulation Analyzer ClotPro® With ROTEM® Delta and Conventional Coagulation Tests in Critically Ill Patients With COVID-19 - Infanger, Lukas; Dibiasi, Christoph; Schaden, Eva; Ulbing, Stefan; Wiegele, Marion; Lacom, Conrad; Gratz, Johannes (Frontiers in Medicine, 2021)
Background: Viscoelastic coagulation testing has been suggested to help manage coagulopathy in critically ill patients with COVID-19. However, results from different viscoelastic devices are not readily comparable. ClotPro® is a novel thromboelastometry analyser offering a wider range of commercially available assays. Methods: We compared the results from ClotPro with results from the well-established ROTEM® Delta device and conventional coagulation tests in critically ill patients with COVID-19. Results: Viscoelastic parameters indicated the presence of a potentially hypercoagulable state in the majority of patients. In up to 95 paired measurements, we found strong correlations between several parameters routinely used in clinical practice: i) EX test vs. EXTEM CT, A5, A10, MCF, ii) IN test vs. INTEM A5, A10, MCF, and iii) FIB test vs. FIBTEM A5, A10, MCF (all R >0.7 and p <0.001). In contrast, IN test CT vs. INTEM CT showed only a moderate correlation (R = 0.53 and p <0.001). Clot strength parameters of both devices exhibited strong correlations with platelet counts and fibrinogen levels (all R >0.7 and p <0.001). Divergent correlations of intrinsically activated assays with aPTT and anti-factor Xa activity were visible. Regarding absolute differences of test results, considerable delta occurred in CT, CFT and clot strength parameters (all p <0.001) between both devices. Conclusions: Several parameters obtained by ClotPro show strong correlations with ROTEM Delta. Due to weak correlations of intrinsically activated clotting times and considerable absolute differences in a number of parameters, our findings underline the need for device-specific algorithms in this patient cohort.